Получение активных слоев InP в составе гетероструктур для диодов Ганна - Vakiv, M. M.; Krukovskiy, S. I.; Zayachuk, D. M.; Mykhashchuk, Iu. S.; Krukovskiy, R. S. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
It is shown that for epitaxial InP layers obtained by liquid-phase epitaxy complex dopping of indium melts by optimal concentrations of rare-earth Yb and isovalent element Al promotes useful increase of cleaning effect from background impurities and leads to growth of its structural perfection. The concentration of electrons in InP layers decreases and their mobility increases on optimal amounts of Yb and Al in the melt. This technology may be used in producing structures for Gunn diodes, photoreceivers and other optoelectronic devices.